The unresolved ethnic question in Uganda’s District Councils - Singiza, D. K.; Visser, J. De (Academy of Science of South Africa, 2015)
The Constitution of Uganda of 1995 (the Constitution) recognises 65 indigenous communities in Uganda. It aspires to integrate all the people of Uganda by directing that "[e]verything shall be done to promote a culture of cooperation, understanding, appreciation, tolerance and respect for each other's customs, traditions and beliefs". The Constitution posits five fundamental rights that are particularly relevant to our discussion. These are: equality and freedom from discrimination; respect for human dignity and protection from inhuman treatment; the protection of freedom of conscience and religion; the protection of minorities; and the right to culture and similar rights. Decentralisation to local government is often associated with two important drivers, namely, deepening democracy and pursuing development. In Uganda, a decentralisation agenda was pursued in order to achieve sustainable levels of development, improve the country's democratic governance, sustain political stability, and promote diversity. This article focuses on Uganda's quest to use decentralisation to promote the accommodation of diversity. It is a critical goal as the neglect or even suppression of diversity, be it ethnic, cultural or religious, can be linked to poverty, political despondency, alienation, and civil strife. It may even result in ethnic groups directly challenging the legitimacy of the state. This article examines the legal and constitutional framework for the election of district councils in Uganda because the design and practice of elections in Uganda has an impact on Uganda's ability to follow through on the promise of respecting and encouraging diversity through decentralisation. The article concludes that the law and practice surrounding the election of district councils reveal the political exclusion of ethnic minorities. It is argued that this is contrary to the stated policy objectives of decentralisation in Uganda and only serves to further promote the political dominance of the ruling party.